Low-energy anomalies in electron tunneling through strongly asymmetric Majorana nanowire - Shkop, A.D.; Parafilo, A.V.; Krive, I.V.; Shekhter, R.I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
Electron transport through Majorana nanowire with strongly asymmetric couplings to normal metal leads is considered. In three terminal geometry (electrically grounded nanowire) it is shown that the presence of unbiased electrode restores zero-bias anomaly even for strong Majorana energy splitting. For effectively two-terminal geometry we show that electrical current through asymmetric Majorana junction is qualitatively different from the analogous current through a resonant (Breit–Wigner) level.